PEMBELAJARAN AKTIF INTEGRATIF BERBANTUAN MS-EXCEL (SPREADSHEET) PELAJARAN RAB MENGHITUNG BIAYA PONDASI RUMAH - Yasin, Mohammad; D.B. Pakpahan, Nurmi Frida; Kusnan, Kusnan (PENDIDIKAN VOKASI:TEORI DAN PRAKTIK, 2015)
ABSTRACT Yasin, Mohammad. 2015. Integrated Active Learning by Microsoft Excel (Spreadsheet) In the Budget Planning Lesson to Count the Cost of a House Foundation. Technology and Vocational Education Study Program, Post Graduate Program of State University of Surabaya. Advisor: (1) Prof.Dr.Kusnan, MT (2) Dr. Nurmi Frida D.B. Pakpahan, M.Pd. Key words: Active Learning, Integrative, Ms-Excel, House Foundation. This research discusses the implementation of the integrated active learning by Microsoft Excel Spreadsheet in the Budget Planning Lesson to Count the cost of a house foundation. This research aims to: (1) find the difference of the students? study result in the budget planning lesson between those who get integrated active learning and those who get convensional learning (lecturung, demonstration); (2) to find the difference of the study result in the budget planning lesson between high successful students and low successful students; (3) to find the interaction between achievment level and learning method toward the study result. The research uses quantitative approach by using factorial design post tes only. The population of the students at SMK N 2 Samarinda at elevenh grade in the third semesters. The data of the studens? success is collected through personality test which is adapted from Edwards Personal Preference Schedule (EPPS). The test of achievment is conducted by objective essay test. The result of the annava F test two talis: (1) the learning method shows the main significant effect for the study result, F(1,56) = 158.680; p < 0.05; (2) the successful level shows the main significant effect for the study result, F(1,56) = 5.612; p < 0.05; (3) there was significant interaction between learning method and level of success of the is not significant interaction between learning method and successful level toward the study result, F(1,56) = 6.848; p